DEVELOPING STRATEGY OF PUBLIC ORGANIZATION : A STUDY OF FACULTY OF SOCIAL SCIENCES AND LAW STATE UNIVERSITY SURABAYA EFFORT INTO STATE UNIVERSITIES LEGAL ENTITIES - Prabawati, Indah; Yani, Muhammad Turhan; Widodo, Bambang Sigit; Harianto, Sugeng (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2022)
The strategic target of education development following the Strategic Plan of the Ministry of Education and Culture 2020-2024 is directed at two things, namely expanding access to education and strengthening the quality and relevance of education. One of the efforts made is to create the independence in higher education through government policies that encourage State Universities (PTN) to become State Universities Legal Entities (PTN-BH) as stipulated in the Regulation of the Minister of Education and Culture Number 88 of 2014 and Regulation of the Minister of Education and Culture Number 4 of 2020 regarding the Change of PTN to PTN-BH. This policy provides an opportunity for the State University of Surabaya (Unesa) to increase its independence status from PTN-BLU to PTN-BH. This study aims to describe the strategy of the Faculty of Social Sciences and Law in welcoming the State University of Surabaya to become a PTN-BH. The research method used in this research is descriptive research using a qualitative approach through document studies using supporting documents to support research activities. The data analysis technique in this study is an interactive model such as data collection, data reduction, data condensation, data presentation, and drawing conclusions. The results of this study indicated that in the attempt to increase its independence into PTN-BH, FISH Unesa applied several strategies namely the arrangement of Unesa FISH Strategic Plan for 2020-2024, Master Plan for Research and Community Service FISH Unesa for 2021-2025, as well as Mapping and Analysis of Human Resources for 2021-2025.